Дослідження впливу використання двозахватних пристроїв на продуктивність роботи РТК - Павленко, І. І.; Мажара, В. А. (ДонНТУ, 2006)
In the given clause the labour productivity of double-ended changer of industrial robots on the position of auxiliary contrivances is considered. The general is classification of auxiliary devices and the structure of their time maintenance by their robots has been considered.